2022
DOI: 10.1111/anae.15668
|View full text |Cite
|
Sign up to set email alerts
|

Major complications of airway management: a prospective multicentre observational study

Abstract: Summary We conducted an observational study of serious airway complications, using similar methods to the fourth UK National Audit Project (NAP4) over a period of 1 year across four hospitals in one region in the UK. We also conducted an activity survey over a week, using NAP4 methods to yield an estimate for relevant denominators to help interpret the primary data. There were 17 serious airway complications, defined as: failed airway management leading to cancellation of surgery (eight); airway management in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…Complications associated with use of an FFP2 or FFP3 respirator were difficult facemask ventilation (OR (95%CI) Audit Project, and a recent Oxford-based study, where rates of severe complications were reported as 1 in 22,000 and 1 in 15,000, respectively [1,22]. Overall, it is difficult to draw a firm conclusion when comparing complication rates with the literature due to differing methodologies and study populations; however, our complication rates appear to fall within a similar range as pre-pandemic studies.…”
Section: Resultsmentioning
confidence: 99%
“…Complications associated with use of an FFP2 or FFP3 respirator were difficult facemask ventilation (OR (95%CI) Audit Project, and a recent Oxford-based study, where rates of severe complications were reported as 1 in 22,000 and 1 in 15,000, respectively [1,22]. Overall, it is difficult to draw a firm conclusion when comparing complication rates with the literature due to differing methodologies and study populations; however, our complication rates appear to fall within a similar range as pre-pandemic studies.…”
Section: Resultsmentioning
confidence: 99%
“…Cumberworth et al. emphasised the over‐representation of obese patients in a cohort of patients analysed using methodology similar to that of NAP4 [25]. Of concern, Cumberworth et al.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of difficult laryngoscopy has been estimated at between 5.8% and 20.5% during thyroid surgery [3][4][5][6][7]. In addition, a recent multicentre observational study illustrated that 35.3% (95%CI 14.2-61.7%) of airway problems were associated with acute or chronic diseases localised in the head, neck or trachea [8].…”
Section: Introductionmentioning
confidence: 99%